Foreword - M. Gail Shroyer; Sally J. Yahnke; Debbie K. Mercer; David S. Allen (Educational Considerations, 2014)
In her examination of Powerful Teacher Education (2006), Linda Darling-Hammond concludes that, “Clearly, a key to dramatically successful preparation of teachers is finding ever more effective ways of connecting the knowledge of the university with the knowledge of the school.”